2012
DOI: 10.7790/ejap.v8i1.320
|View full text |Cite
|
Sign up to set email alerts
|

Job stress, wellbeing, work-life balance and work-life conflict among Australian academics

Abstract: Escalating stress and pressures, along with organisational change in universities has led to the increased importance of research in to the impact of perceived job stress, work-life balance and work-life conflict amongst academics. Yet, very few studies have examined academics' ability to balance work and personal life, and overcome work-life conflict. Drawing on Spillover theory (Zedeck, 1992), our study hypothesised that high levels of perceived job pressure stress and job threat stress would predict increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(242 citation statements)
references
References 74 publications
10
162
0
23
Order By: Relevance
“…While the issue of balancing between work-life has come into the lime light, the reality is, employees are constantly juggling between to keep a balance between their professional and personal life [1]. According to Tomazevic, Kozjek and Stare (2014) the meaning of work-life balance is to effectively combining professional life with personal obligations and creates a harmony between these two aspects [2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While the issue of balancing between work-life has come into the lime light, the reality is, employees are constantly juggling between to keep a balance between their professional and personal life [1]. According to Tomazevic, Kozjek and Stare (2014) the meaning of work-life balance is to effectively combining professional life with personal obligations and creates a harmony between these two aspects [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Tomazevic, Kozjek and Stare (2014) the meaning of work-life balance is to effectively combining professional life with personal obligations and creates a harmony between these two aspects [2]. It can be defined as the absence of conflict between professional and personal life [1]. According to Amstad et al (2011) work interfering with family is more associated with work related outcomes than family related outcomes [3].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-life conflict occurs when work and non-work demands are incompatible (Rana & Panchal, 2014). Bell, Rajendran and Theiler (2012) found that escalating stress and pressures related to the changing higher educational environment affects the work-life balance of academic staff. A study by Noor (2011) showed that satisfaction with work-life balance was a significant predictor of academic turnover intentions in Malaysian public HEIs.…”
Section: Flexible Working Hours (Work-life Balance)mentioning
confidence: 99%
“…The combined responsibilities of teaching, research and community service coupled with work overload are reported as the most signiicant determinants of stress among this population [44]. Other signiicant stressors include emotion work [45]; email related stress [46]; worklife conlict [30,47,48] job insecurity/lack of tenure and bullying cultures. Increased student numbers and student diversity coupled with decreased student staf ratios [13] and increased student expectations can make it diicult for academics to balance competing demands.…”
Section: Stress Among Academicsmentioning
confidence: 99%